Uji Kadar Timbal (Pb) pada Ikan Teri dan Cumi Kering yang Beredar di Pasar Sambu Medan secara Spektrofotometri Serapan Atom - Hendri Faisal; Fitria Wati; Dwi Setio Purnomo (Jurnal Indah Sains dan Klinis, 2021)
Anchovies and squid are some of the most abundant fishery resources in Indonesian waters. There is an increase in the concentration of heavy metals such as lead in marine waters which is caused by industrial waste, both solid and liquid waste, so that marine biota such as anchovies and squid accumulate these heavy metals. The very high level of heavy metal toxicity can have adverse effects on public health. The aim of this study was to determine the lead content and determine the number of levels in dried anchovies and dried squid circulating in Sambu Market, Medan City. This research used the atomic absorption spectrophotometric method at a wavelength of 283.8 nm. The results showed that dried anchovies and dried squid contained lead with the highest levelsin dried anchovies was 7.04 mg/kg and the levels in dried squid were 6.65 mg/kg. The metal content of lead in dried anchovies and dried squid has exceeded the maximum standard set by the Indonesian National Standard (SNI Number 7387 of 2009), namely 0.3 mg/kg in fish and their processed products, while 1.5 mg/kg in mollusks.